KOMUNIKASI POLITIK YOPI ARIANTO DALAM MEMENANGKAN PEMILIHAN UMUM KEPALA DAERAH KABUPATEN INDRAGIRI HULU TAHUN 2015 - Syahlia Rinjani; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
2015 is a party of democracy for Indragiri Hulu community. Yopi Arianto, SE as incumbent candidate successfully re-elected to Regent Indragiri Hulu period 2015-2020 period. This study aims to determine the style of communication polittik Yopi Arianto and the use of media in the campaign in the election of regional head of Indragiri Hulu Regency in 2015. The method of this research is qualitative research method. The informants in this study consisted of Yopi Arianto as Indragiri Hulu District Head, 2 people, and 1 successful team. Techniques of collecting interview data, observation, and documentation. The results of this study indicate that the victory back Yopi Arianto became Regent Indragiri Hulu Regency in 2015 can be achieved with political communication that he did. This political communication includes the style of political communication as well as the use of media in the campaign. Political communication style Yopi Arianto is known as an energetic, interactive, and close to the people. In addition, the selection of media use in campaigns is also a matter of concern. Yopi Arianto uses some media of kampaye covering media directly or face to face ie communication directly to society, social media in form of facebook which is useful to convey information about activity during campaign progress. In addition, the use of outdoor media such as banners, billboards and banners and the use of small format media in the form of posters, clocks, calendars and T-shirts is also a concern Yopi Arianto in attracting the public to vote himself back in the elections of regional heads in 2015 Regency of Indragiri Hulu.Keyword: Local Election, Political Communication